Research Advances in Amorphous‐Crystalline Heterostructures Toward Efficient Electrochemical Applications. Issue 10 (16th December 2022) - Jin, Yachao; Zhang, Mengxian; Song, Li; Zhang, Mingdao
Abstract: Interface engineering of heterostructures has proven a promising strategy to effectively modulate their physicochemical properties and further improve the electrochemical performance for various applications. In this context related research of the newly proposed amorphous‐crystalline heterostructures have lately surged since they combine the superior advantages of amorphous‐ and crystalline‐phase structures, showing unusual atomic arrangements in heterointerfaces. Nonetheless, there has been much less efforts in systematic analysis and summary of the amorphous‐crystalline heterostructures to examine their complicated interfacial interactions and elusory active sites. The critical structure‐activity correlation and electrocatalytic mechanism remain rather elusive. In this review, the recent advances of amorphous‐crystalline heterostructures in electrochemical energy conversion and storage fields are amply discussed and presented, along with remarks on the challenges and perspectives. Initially, the fundamental characteristics of amorphous‐crystalline heterostructures are introduced to provide scientific viewpoints for structural understanding. Subsequently, the superiorities and current achievements of amorphous‐crystalline heterostructures as highly efficient electrocatalysts/electrodes for hydrogen evolution reaction, oxygen evolution reaction, supercapacitor, lithium‐ion battery, and lithium‐sulfur battery applications are elaborated. At the end of this review, future outlooks and opportunities on amorphous‐crystalline heterostructures are also put forward to promote their further development and application in the field of clean energy. Abstract : The emerging amorphous‐crystalline heterostructures with distinctive atomic arrangement at the heterointerfaces are promising candidates for next‐generation high‐performance electrocatalysts/electrodes. This review discusses for the first time these ever‐increasing novel multifunctional nanomaterials toward various electrochemical applications, aiming to offer cross‐sectional insights into the structure‐property relationships and provide guidance for the rational design of amorphous‐crystalline heterostructures with desired performance.